Math, asked by Sukhchani, 1 year ago

using suitable identity, evaluate 13^3 - 6^3 - 7^3​

Answers

Answered by StarGazer001
24

Question \:  =  >  \:  \:

 {13}^{3}  -  {6}^{3}  -  {7}^{3}

Answer \:  =  >  \:

 {a}^{3}  +  {b}^{3}  +  {c}^{3}  = 3abc

[If a+b+c=0]

a = 13 , b=-6 , c=-7

13-6-7 => 13-13 => 0

Therefore \:  \: {a}^{3}  +  {b}^{3}  +  {c}^{3}  = 3abc

= 3.13.(-6).(-7)

= 39(42)

= 1638

 \boxed{Answer \:  =  >  \: 1638}

Answered by anjug0658
0

Answer:

1638

Step-by-step explanation:

Question=>

{13}^{3} - {6}^{3} - {7}^{3}13

3

−6

3

−7

3

Answer \: = > \:Answer=>

{a}^{3} + {b}^{3} + {c}^{3} = 3abca

3

+b

3

+c

3

=3abc

[If a+b+c=0]

a = 13 , b=-6 , c=-7

13-6-7 => 13-13 => 0

Therefore \: \: {a}^{3} + {b}^{3} + {c}^{3} = 3abcThereforea

3

+b

3

+c

3

=3abc

= 3.13.(-6).(-7)

= 39(42)

= 1638

Similar questions